Intraocular pressure changes during vitrectomy using constellation vision system's intraocular pressure control feature - Falabella, Paulo; Stefanini, Francisco; Lue, Jaw-Chyng; Pfister, Marcel; Reyes-Mckinley, Jahlyn; Koss, Michael Janusz; Teixeira, Anderson; Schor, Paulo; Humayun, Mark (Retina, 2016)
Purpose:To evaluate intraocular pressure (IOP) changes during experimental vitrectomy and the efficacy of Constellation Vision System's IOP control (IOPc) feature in reestablishing baseline pressure.Methods:Using a pressure transducer in freshly enucleated porcine eyes, a broad range of parameters (
Gesehen am 18.06.2020